Benefits of a Proactive Office Ergonomics Program. (September 2013) - Hedge, Alan
Ergonomics surveys were conducted in a software company with a proactive ergonomics program before and after moving to a new headquarters building in which workstations were equipped with ergonomic products. Sixty-seven workers voluntarily completed surveys of their workstations, workplace environment, work-related health and well-being (job satisfaction, happiness). Post-move results showed that after moving to the ergonomic workstations the prevalence of musculoskeletal discomfort was reduced, overall satisfaction with workstations improved, and employees were happier and more satisfied with their job.